PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF KELAS III SD NEGERI 21 PONTIANAK BARAT - AR, Nadhirah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to describe improving student learning outcomes in mathematics using manipulative media in the Class III SD Negeri 21 Pontianak West.The method used in this research is descriptive. Forms of research is classroom action research. The nature of research is collaborative. The subject of this study were teachers as researchers and 36 third grade students of SD Negeri 21 Pontianak West consisted of 14 female students and 22 male students research procedure includes four stages: Planning, Implementing, Observations and Reflections. This research was conducted as much as two cycles. Results of the study are: 1) the ability of teachers in planning lessons in cycle 1 average of 3.34 increased to 3.92 in the second cycle. 2) the ability of teachers in implementing the learning in the first cycle, an average of 3.26 increased to 3.98 in the second cycle 3) An increase in the average learning outcomes of the third class in the first cycle average of 65.83 increased to 93.61 in the second cycle. The conclusion of this study is there an increase of students mathematics learningâ€™s outcomes using manipulative media class III SD Negeri 21 West Pontianak. Keywords: Media Manipulatives, learning Outcomes, Math. Â